Penerapan Agile Extreme Programming untuk Optimasi Layanan Pemesanan Menu Digital pada Mogano Coffee and Space - Ismiyana Putri, Dwi; Pradana, Jovanca Rega; Baydhowi, Muhamad (Bahasa Indonesia, 2025)
Intense competition in the food and beverage industry compels business actors to enhance both operational efficiency and service quality. Mogano Coffee and Space faced challenges with its manual ordering process, resulting in long queues and difficulties in tracking orders. This study aims to design and implement a web-based menu ordering information system using the Extreme Programming (XP) method, one of the Agile development approaches. The system was developed through the stages of planning, design, coding, and testing. The results indicate that the developed system successfully improved operational efficiency, reduced queues, and enhanced user experience. Alpha and beta testing, along with user evaluation, showed a high level of satisfaction with the system’s ease of use and transaction speed, achieving a satisfaction rate of 94%. These findings support the effectiveness of XP implementation in developing information systems within the food and beverage sector.